(3Pjd GdcJGH PNjQI GdWGdH HeG GdedYe WGdH ef BOGH heBQHs - (3eLghds
(3ChdgG (B:s
(3GdMeO ddg GdPi Yde agPG eG JjSQ EdMGbg HPNjQI GdWGdH LYdgG cCUdgG fGab hdcd ShA OGab hYfg Udi Gddg Ydjg hSde eG YHO Gddg HTF CaVd ef abg ai MOjK hdabjg hGMO CTO Ydi GdTjWGf ef Cda YGHO s
(3BNQgG (B:s
(3ef bQG GPG aQZ ef UdGI GdaQV SHM GSe QHc GdGYdi aEPG GfJgi Edi SfbQFc adG JfSi hGdMeO ddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3JHUQI GdYfhGf (B:s
(3JPjjds
Keywords: (3GdSjGSI hGdGLJeGYs